Influence of lactational status of the surrogate mare during early pregnancy on inflammatory markers in subsequently born foals - Affonso, Fernanda Jordão; Alonso, Maria Augusta; Bringuel, Beatriz Alves; Douglas, Robert Hazourd; de Paula Nogueira, Guilherme [UNESP]; Fernandes, Claudia Barbosa (Elsevier, 2023)
Nutrition during pregnancy has a significant impact on the offspring and affects health, growth and metabolism in several species, including equines. Studies have associated orthopedic problems in foals, such as osteochondritis dissecans (OCD), with diet of the broodmare during pregnancy resulting in high glucose concentrations, causing suppression of the central regulation of growth hormone (GH) secretion and subsequent disruption of the GH/IGF-1 (insulin-like growth factor-1) axis. It is very common to use non-lactating mares as embryo recipients, however little is known about the effect of lactational status on pregnant mare metabolism and the effect on the resulting embryo, fetus and the offspring's metabolism and development. Our study aimed to compare inflammatory cytokines, osteocalcin and IGF-1 in foals born from lactating recipient mares (LM; n=7) and non-lactating recipient mares (NLM; n=5) from days 1-28 after birth. Twelve healthy Mangalarga Paulista mares aged 5 to 15 years of age were used. Twelve foals, eight males and four females, born by eutocia were evaluated. Recipient LMs were lactating from the day of ovulation, until a maximum of 170 days of pregnancy (124 to 170). Foal evaluations were performed at birth (D1) and at 7, 14, 21 and 28 days of age (D7, D14, D21 and D28). Leptin (ng/mL), adiponectin (µg/mL), resistin (ng/mL) analyses were performed using ELISA, and interleukin6 (IL6; pg/mL), interleukin 10 (IL10; pg/mL), tumor necrosis factor (TNFα; pg/mL), osteocalcin (ng/mL) and IGF-1 (ng/mL) were evaluated using immunoassay kits. We used a factorial arrangement between group (LM x NLM) and time (D1, D7, D14, D21 and D28). The results are the mean and standard error of the mean. There was no significant interaction in any of the variables. Concentrations of IGF-1, IL6, IL10 and TNFα were higher in the NLM group (IGF1: 29.48±3.82 vs 176.53±65.8, p=0.0002; IL6:9.89±0.74 vs 13.57±1.33, p=0.01; IL10: 75.37±3.89 vs 100.75±8.84, p=0.0006 and TNFα: 8.08±1.08 vs 12.89±1.75, p<0.001). Only in IL10 concentration, there was a difference over time (D1: 114.11±1.04; D7: 72.08±8.13; D14: 12±6.96; D21: 72.98±5.25 and D28:100.44±9.25; p<0.001). Osteocalcin correlated positively with leptin (p<0.05; r=0.27). In this study, the recipient mares’ lactational status during the first trimester of pregnancy influenced concentrations of inflammatory markers in the subsequently born foal up to 28 days of life, with higher concentrations of IGF-1, IL6, IL10 and TNFα than in foals born from non-lactating recipient mares. This raises an important discussion on the impact of lactational status of the recipient dam on the future of her offspring. Acknowledgements: FAPESP (2017/05425-0 and 2020/10260-3) and CAPES